Pengaruh Customer Brand Love melalui Genuineness Personal Branding terhadap Loyalitas Konsumen Gen-Z pada Coffeeshop di Kota Mataram - Kalbuadi, Amiruddin; Kembang, Lale Puspita; Hermanto, Agus; Hilmawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This research examines the influence of customer brand love and the mediating role of genuineness of personal branding on consumer loyalty among Gen-Z coffee shop patrons in Mataram City. With Gen-Z prioritizing authenticity and value alignment, the research investigates how emotional connections and perceived brand genuineness shape loyalty in a competitive market. A quantitative approach using structural equation modeling (SEM) with 384 respondents revealed significant direct effects: customer brand love positively influences both genuineness of personal branding and consumer loyalty. Additionally, the genuineness of personal branding directly impacts loyalty. Notably, genuineness of personal branding mediates the relationship between customer brand love and customer loyalty, explaining 30% of the total effect. The findings highlight that authentic personal branding amplifies emotional bonds, which in turn drive loyalty. The study underscores strategies for coffeeshops to foster Gen-Z loyalty by prioritizing transparent communication, experiential engagement, and values-driven narratives. Practical implications emphasize the need for brands to align with Gen-Z’s demand for authenticity to enhance competitiveness.